Tônus da presença : experiência estética como jogo, quietude e contingência - Mariana Lage Miranda (2015)
This thesis investigates the nature of contemporary aesthetic experience and proposes a constellation of concepts in order to direct the philosophical approach of art towards a perspective open to the contingent, play, event, performance, sensory experience, and epiphanic pleasure.Instead of an Aesthetics that focuses on the notions of work of art, art world, fiction – or which believes that the role of contemporary art is repeatedly put the question “is it art?” and “why is this art?” – I advocate the primacy of the aesthetic experience as lived experience [Erlebnis], as body engagement, and as tone of presence. Discussing the concepts of performance by Paul Zumthor and of presence by Hans Ulrich Gumbrecht, I relate them with numerous examples of contemporary art, like John Cage (1952) and Marina Abramovic (2014), proposing that the experience happens less as apprehension of a meaning, and more as an epiphany, as a contingent form, and as a transient, incommunicable pleasure. From Gumbrecht’s writings on presence, this work inherits the importance of Heidegger's Gelassenheit for the foundation of a tone of presence: a state of being available, relaxed and with the senses awake, for the here and now presence. In an age in which we live the disarticulation of historical chronological time, in which emerges feelings of cronophobia, of an eternal now and of a large present, the tone of presence draws attention to a more bodily and spatial aesthetic experience, more given to what is present.